Tailoring Exciton Dynamics by Elastic Strain‐Gradient in Semiconductors. (27th January 2014) - Fu, Xuewen; Su, Cong; Fu, Qiang; Zhu, Xinli; Zhu, Rui; Liu, Chuanpu; Liao, Zhimin; Xu, Jun; Guo, Wanlin; Feng, Ji; Li, Ju; Yu, Dapeng
<x xml:space="preserve">Abstract</x> In purely bent ZnO microwires, the excitons can be effectively driven and concentrated by the elastic strain‐gradient towards the tensile outer side of the purely bent wire. Experimental and theoretical approaches are combined to investigate the dynamics of excitons in an inhomogeneous strain field with a uniform elastic strain‐gradient. Cathodoluminescence spectroscopy analysis on purely bent ZnO microwires verifies that excitons can be effectively driven and concentrated along the elastic strain‐gradient. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>